In vivo activation of pH-responsive oxidase-like graphitic nanozymes for selective killing of Helicobacter pylori - Lufeng Zhang (Nature Portfolio, 2021)
Helicobacter pylori is a major cause of gastric diseases, but the standard therapy is limited by continuously decreased therapeutic efficacy and side effects to symbiotic bacteria. Here, the authors develop a pH-responsive graphitic nanozyme that is active under low pH gastric conditions, but inactive in intestines, for selective treatment of H. pylori infections.